Predicting AURKA as a novel therapeutic target for NPC: A comprehensive analysis based on bioinformatics and validation - Huang, Chaobin; Chen, Lin; Zhang, Yiping; Wang, Liyan; Zheng, Wei; Peng, Fengying; Xu, Yuanji (Frontiers in Genetics, 2022)
This study comprehensively explored the clinical function of Aurora kinase A (AURKA) gene in nasopharyngeal carcinoma (NPC) and analyzed its potential as a therapeutic target in cancer. Data were downloaded from GEO, STRING, GTEx, and CellMiner databases, and subjected to multiple bioinformatic analyses, including differential expression analysis, WCGNA, gene ontology (GO), Kyoto encyclopedia of genes and genomes (KEGG), gene set enrichment analysis (GSEA), gene set variation analysis (GSVA), miRNA-hub gene regulatory network analysis, immune cell infiltration, and drug sensitivity analysis. In-depth analysis of AURKA gene expression in NPC and its corresponding clinicopathological features was performed to explore its potential as a therapeutic target. Moreover, AURKA gene expression in NPC was validated by qRT-PCR in 21 NPC tissues and 17 normal nasopharyngeal epithelial tissues. AURKA was highly expressed in NPC tissues. Enrichment analysis of AURKA and its co-expressed hub genes indicated their oncogenic role in NPC and their potential involvement in cancer-promoting processes through histone kinase activity and microtubule motility activity, cell cycle, and p53 signaling pathways. AURKA high expression group had greater infiltration of neutrophils, macrophages M2, and dendritic cells resting and less infiltration of T cells CD4+ naïve and T cells γδ. Drug susceptibility analysis found that dacarbazine, R-306465, vorinostat, and other antitumor drugs that act on the cell cycle were closely related to AURKA. qRT-PCR verified the high expression of AURKA in NPC tissues (p < 0.05). We confirmed upregulation of AURKA in NPC tissues. Our results support an oncogenic role of AURKA in the context of NPC, and indicate its potential role as a novel therapeutic target.